Sizing PZT Transducers in Impedance-Based Structural Health Monitoring - Baptista, Fabricio G.; Vieira Filho, Jozué [UNESP]; Inman, Daniel J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
A theoretical and experimental analysis regarding the correct size of PZT (Lead Zirconate Titanate) transducers used in structural health monitoring (SHM) systems based on the electromechanical impedance (EMI) technique is presented. Tests were carried out on aluminum structures using 5A and 5H PZT patches of various sizes. The results show that the sensitivity of SHM systems for damage detection can be optimized if the transducers are correctly sized according to the proposed procedure.
Keywords: Electromechanical impedance; PZT ceramics; structural engineering; structural health monitoring (SHM)